2012
DOI: 10.1134/s1063773712100027
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the veiling of the photospheric spectrum for T Tauri stars in terms of an accretion model

Abstract: The problem on heating the atmospheres of T Tauri stars by radiation from an accretion shock has been solved. The structure and radiation spectrum of the emerging so-called hot spot have been calculated in the LTE approximation. The emission not only in continuum but also in lines has been taken into account for the first time when calculating the spot spectrum. Comparison with observations has shown that the strongest of these lines manifest themselves as narrow components of helium and metal emission lines, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…According to Muzerolle et al (2003) emission of dust component of protoplanetary disk gives noticeable excess relative to the photospheric radiation only at wavelengths λ > 2 µm, so to explain observed veiling near 1 µm Fischer et al (2011) have suggested that there is an additional source of the continuum emission with temperature 2500-5000 K. Gahm et al (2008) found from the analysis of highly veiled CTTS's spectra that emission lines, which are formed in the accretion spot along with continuum, contribute significantly to decreasing of photospheric line's depth. Dodin & Lamzin (2012) confirmed this discovery by theoretical modeling and also demonstrated that "veiling by lines" is important for both CTTS with high and small veiled spectra. Moreover they found that at given effective temperature of the star T ef the relative contribution of lines to veiling increases with decreasing of accretion flux, which is defined by the relation F ac = ρ 0 V 3 0 /2, where ρ 0 and V 0 are pre-shock gas density and velocity respsectively.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…According to Muzerolle et al (2003) emission of dust component of protoplanetary disk gives noticeable excess relative to the photospheric radiation only at wavelengths λ > 2 µm, so to explain observed veiling near 1 µm Fischer et al (2011) have suggested that there is an additional source of the continuum emission with temperature 2500-5000 K. Gahm et al (2008) found from the analysis of highly veiled CTTS's spectra that emission lines, which are formed in the accretion spot along with continuum, contribute significantly to decreasing of photospheric line's depth. Dodin & Lamzin (2012) confirmed this discovery by theoretical modeling and also demonstrated that "veiling by lines" is important for both CTTS with high and small veiled spectra. Moreover they found that at given effective temperature of the star T ef the relative contribution of lines to veiling increases with decreasing of accretion flux, which is defined by the relation F ac = ρ 0 V 3 0 /2, where ρ 0 and V 0 are pre-shock gas density and velocity respsectively.…”
Section: Introductionsupporting
confidence: 67%
“…As the result dependence of the total (lines+continuum) veiling on wavelength in optical band becomes non-monotonic instead of monotonic in the case of veiling by continuum only -see Fig. 7 in Dodin & Lamzin (2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations